The bioarchaeology of classical Kamarina life and death in Greek Sicily - Sulosky Weaver, Carrie L. (Bioarchaeological interpretations of the human past: local, regional, and global perspectives, 2015)
Weaver explores the mortuary practices, health and disease, and even the magical beliefs of classical Kamarina using a comparative approach to analyze grave goods and burial positions